PENGARUH PEMBIAYAAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA UTARA - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The objective of this research was to determine the influence of Islamic Financing.for Growth in , h Sumatra. The analysis method used in this research is the method of Ordina,y Least Square (OLS) regression testing simple. The variable in this study is Islamic Financing (X) and Growth (Y) in North Sumatra. The data used is seconda,y data derived from Islamic Banking Statistics Bank Indonesia and Economic Growth Data from the Central Statistics Agency f (BPS) o North Sumatra with the observation period May 1, 2014 until March 1, 2015. Results of this study prove that Sharia financing significant effect on economic growth in North Sumatra. It is an input to the national banking authorities, especially Bank Indonesia and the Financial Services Authority (OJK) where the future fi1rther.